Keanekaragaman Hayati Tumbuhan Lumut (Bryophyta) Sekitar Kebun Rojo Camp Kecamatan Dau Kabupaten Malang - Ajeng Dewi Masyitoh; Ika Saputri; Ike Rahma Antika; Feren Aisya Ifannani; Lidya Amelia Simanjuntak; Nabila Rahma Safitri; Indra Fardhani (Postgraduate, University of Mataram, 2023)
Moss plants (Bryophyta) are living things that include multi-celled green plants. Growing mosses (Bryophyta) are known to have a simple arrangement of organs. This study examines the biodiversity of moss plants which aims to determine the biodiversity of moss plants found around Rojo Camp Gardens, Dau District, Malang Regency. This study uses the observation method to collect data by direct observation. This method is used as an observation of the object of research, especially on the focus of the problem under study. The data obtained was in the form of the number of species and body morphological characteristics of the moss plant species. The results of the study found that 7 types of moss plants were found with different body morphologies. The special characteristics of moss plants are that they have rhizoids and leaves, but do not yet have true roots, stems and leaves. Moss plants have a role in ecosystems, including as water absorbers (the nature of their cells resembles sponges), to retain moisture, produce oxygen through a fast photosynthetic process and as pollutant absorbers so that these moss plants can be found around Rojo Camp Gardens, Dau District, Malang Regency.